2019
DOI: 10.1002/jcp.28765
|View full text |Cite
|
Sign up to set email alerts
|

Expression analysis of circulating plasma long noncoding RNAs in colorectal cancer: The relevance of lncRNAs ATB and CCAT1 as potential clinical hallmarks

Abstract: Long noncoding RNAs (lncRNAs) have been demonstrated to regulate a variety of cell processes and involve in the development and progression of colorectal cancer (CRC).Recently, the circulating lncRNAs have emerged as minimally invasive biomarkers for cancer diagnosis and prognosis. We aimed to examine the plasma expression level of long noncoding RNAs lnc-ATB, lnc-CCAT1, and lnc-OCC-1 in CRC patients and evaluate the clinical values. A total of 74 pretreatment CRC and 74 healthy blood biopsies were subjected t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(25 citation statements)
references
References 17 publications
(29 reference statements)
1
23
0
Order By: Relevance
“…lncRNAs were once considered to be a noisy byproduct of the transcription process (24). However, previous studies have reported that lncRNAs serve an important role at the RNA level in regulating cell proliferation, differentiation, the maintenance of pluripotent stem cells and cancer pathogenesis (25,26). The present study aimed to identify the lncRNAs associated with glioma, and subsequently used bioinformatics to analyze the biological functions and signal transduction pathways involved in the regulation of the lncRNAs identified.…”
Section: Discussionmentioning
confidence: 99%
“…lncRNAs were once considered to be a noisy byproduct of the transcription process (24). However, previous studies have reported that lncRNAs serve an important role at the RNA level in regulating cell proliferation, differentiation, the maintenance of pluripotent stem cells and cancer pathogenesis (25,26). The present study aimed to identify the lncRNAs associated with glioma, and subsequently used bioinformatics to analyze the biological functions and signal transduction pathways involved in the regulation of the lncRNAs identified.…”
Section: Discussionmentioning
confidence: 99%
“…The higher expression of UNC5B-AS1, MATAL1 and n340790 was shown to distinguish the tumor and normal samples with AUC values of 0.932, 0.632 and 0.845, respectively (127,130,131). With the increasing identification of diagnostic circulating lncRNAs in different cancers (173)(174)(175)(176)(177), we expect to see the utilization of circulating lncRNAs to optimize diagnostic accuracy of thyroid nodules in the future.…”
Section: Ncrnas Are Novel Candidates For Early Detection Of Thyroid Cmentioning
confidence: 94%
“…It is reported that several lncRNAs are aberrantly expressed in tissue or serum from colorectal cancer patients. Some studies have reported that MEG3 [9], lnc-ATB [10] and BLACAT1 [11] were up-expressed in colorectal cancer plasma, while NKILA [7] and HOTAIRM1 [12] were down-regulated in colorectal cancer tissue. A sensitivity of 37.16% and a specificity of 88.75% for CEA were significantly lower than that for exosomal CRNDE-h (P < 0.001) [13].…”
Section: Ivyspringmentioning
confidence: 99%
“…The expression levels of LncRNAs were determined using quantitative real-time polymerase chain reaction (qRT-PCR). Seven types of lncRNAs were recognized as tumor promoters [10,11,13,14,[21][22][23][24][25] and six were tumor suppressors [7,9,[26][27][28][29] in CRC patients. The associations between lncRNAs and clinicopathologic parameters in CRC patients are shown in Table 1.…”
Section: Study Parameters and Study Qualitymentioning
confidence: 99%